THE EFFECTS OF CHANGES IN MINIMUM WAGE ON EMPLOYMENT IN THE COVERED AND UNCOVERED SECTORS IN INDONESIA - Pratomo, Devanto Shasta (Journal of Indonesian Economy and Business, 2010)
This study examines the effects of changes in minimum wage on employment in the covered and uncovered sectors in Indonesia using an individual micro-level data set from1989 to 2003. Since the Indonesian Labor Force Survey data are not a panel, this study applies pooled cross-sectional time-series methodology to explore the impact of theminimum wage across individual workers. All of the equations are analyzed separately in urban and rural labor markets, as well as the male and female labor market. The results suggest that an increase in minimum wage is more likely to decrease the covered sector employment and to increase the uncovered sector employment. These results also indicate a displacement effect from the covered sector to the uncovered sector, as suggested by the two-sector model. In addition, this study found the displacement effect is stronger for women, indicating that female workers are the more likely to be hurt as the result of an increase in minimum wage. Compared to urban areas, the effects in rural areas are somewhat lower, indicating that minimum wage is less binding, given the dominance of thetraditional agriculture sector.Keywords: Minimum Wage, Employment, Covered Sector, Uncovered Sector